Mental, Physical and Mixed Practice Effects on Elderly Static and Dynamic Balance - Mohammad Ali Aslankhani; Amir Shams; Parvane Shamsipour Dehkordi (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: After age of 65, annually 10 percent of older adults> loss their independent in one or more daily task. Because of decreasing changes in neuromuscular system that is important factor in loss the balance and walking ability in this group of people. In according to these sentences, the aim of this research was to the comparison of mental, physical and mixed practices on static and dynamic balance in health older adults. Methods & Materials: The study is semi-experimental with pre and post test design and three experimental groups. Statistical sample included 60 older adults> with age range of 60-70 years from Shahre-kord, that randomly divided to three experimental groups. In this research, the Stroke stands test (standing with one leg) were used to measure the static balance and Star Excursion Balance Test (SEBT) test was used to measure the dynamic balance. After 8 session of training, subject of each group participated in post test that similar to pretest. The data were analyzed by one way ANOVA and Tukey post hoc and in order to detect the homogeny of variances, Leaven>s test was used in level of P<0.05. Results: Statistical results in three training methods (mental, physical and mixed) in static and dynamic balance showed significant difference between groups performance in post test. Further, result of Tukey post hoc show that there is significant difference between mixed group with other groups (P<0.001) and subjects in this group had a better performance than other groups. Furthermore, the performance of physical practice group was better than mental practice group (P<0.029). Conclusion: according to result of percent study that show improvement in static and dynamic balance in mixed group, it could be concluded that, for increase in muscle strength in lower extremity and promote older adults> balance by strength training, coaches and related affairs can use this training method in their specific programs for older adults.